PERAN RISET DAN PENGEMBANGAN (R&D) AKADEMIS TERHADAP PERTUMBUHAN EKONOMI - Khaliq, Abdul (Jurnal Ekonomi Kuantitatif Terapan; 2020: Vol. 13, No. 1, Februari 2020 (pp. 1-210), 2020)
This study empirically examines the role of research and development (R&D) in the universities on economic growth. Using yearly data over the period 1996-2013 for 32 advanced economies and 46 developing countries in the world, the empirical results are estimated by static- and dynamic-panel data to provide evidence in favor of the impact of academic research and development on economic growth. The empirical evidence suggests that the static- and dynamic-panel data analysis estimates well characterize how academic research and development (R&D) influences economic growth in advanced economies and developing countries. Static panel data analysis in the light of fixed effect method (FEM) suggest positive effect of academic research and development on economic growth both in advance economies and developing countries. Moreover, dynamic panel data (Arrelano-Bond and Blundell-Bond) analysis finds academic research and development has consistently positive effect on economic growth in advanced economies, unfortunately academic R&D has negative effect on economic growth in developing countries. Based on the results, this study recommends for developing countries especially Indonesia to pay specific attention to academic R&D at universities by commercialization of new inventions and knowledge to attract industry.